The Anthelmintic Quassinoids Ailanthone and Bruceine a Induce Infertility in the Model Organism Caenorhabditis elegans by an Apoptosis-like Mechanism Induced in Gonadal and Spermathecal Tissues - Nicola Knetzger; Viktoria Bachtin; Susanne Lehmann; Andreas Hensel; Eva Liebau; Fabian Herrmann (Molecules, 2021)
In continuation of the search for new anthelmintic natural products, the study at hand investigated the nematicidal effects of the two naturally occurring quassinoids ailanthone and bruceine A against the reproductive system of the model nematode Caenorhabditis elegans to pinpoint their anthelmintic mode of action by the application of various microscopic techniques. Differential Interference Contrast (DIC) and the epifluorescence microscopy experiments used in the presented study indicated the genotoxic effects of the tested quassinoids (c ailanthone = 50 µM, c bruceine A = 100 µM) against the nuclei of the investigated gonadal and spermathecal tissues, leaving other morphological key features such as enterocytes or body wall muscle cells unimpaired. In order to gain nanoscopic insight into the morphology of the gonads as well as the considerably smaller spermathecae of C. elegans, an innovative protocol of polyethylene glycol embedding, ultra-sectioning, acridine orange staining, tissue identification by epifluorescence, and subsequent AFM-based ultrastructural data acquisition was applied. This sequence allowed the facile and fast assessment of the impact of quassinoid treatment not only on the gonadal but also on the considerably smaller spermathecal tissues of C. elegans. These first-time ultrastructural investigations on C. elegans gonads and spermathecae by AFM led to the identification of specific quassinoid-induced alterations to the nuclei of the reproductive tissues (e.g., highly condensed chromatin, impaired nuclear membrane morphology, as well as altered nucleolus morphology), altogether implying an apoptosis-like effect of ailanthone and bruceine A on the reproductive tissues of C. elegans.